2014
DOI: 10.1039/c4an01272k
|View full text |Cite
|
Sign up to set email alerts
|

Chemical sensing with nanoparticles as optical reporters: from noble metal nanoparticles to quantum dots and upconverting nanoparticles

Abstract: A wide variety of biological and medical analyses are based on the use of optical signals to report specific molecular events. Thanks to advances in nanotechnology, various nanostructures have been extensively used as optical reporters in bio- and chemical assays. This review describes recent progress in chemical sensing using noble metal nanoparticles (gold and silver), quantum dots and upconverting nanoparticles. It provides insights into various nanoparticle-based sensing strategies including fluorescence/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 130 publications
0
39
0
Order By: Relevance
“…Among metal NPs, gold (Au) and silver (Ag) NPs are the most widely studied due to their numerous applications as sensors, nanocarriers, and in cosmetics [35], among others. The applicability of these NPs stems from their visible absorption bands, straightforward method of synthesis (with high degree of size and shape control), stability, biological compatibility, and easy functionalization with various (bio)molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Among metal NPs, gold (Au) and silver (Ag) NPs are the most widely studied due to their numerous applications as sensors, nanocarriers, and in cosmetics [35], among others. The applicability of these NPs stems from their visible absorption bands, straightforward method of synthesis (with high degree of size and shape control), stability, biological compatibility, and easy functionalization with various (bio)molecules.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of all these advantages, it is possible to find out in the literature numerous demonstrations of the potential application of UCNPs for both in vitro and in vivo high contrast imaging as well as for biodetection and biosensing applications. 3,[10][11][12][13] Indeed, UCNPs are becoming one of the most interesting nanosized luminescent probes and a careful bibliographic research revealed that almost 10 % of all the papers published in the literature dealing with the use of fluorescent nanoparticles for bioimaging are involving them. In many of these applications, local information of the biosystem under study is obtained after a detailed spectral analysis of the luminescence generated by UCNPs.…”
mentioning
confidence: 99%
“…Composite nanostructures based on noble metal nanoparticles (NPs) and semiconductor nanocrystals, or quantum dots (QDs), are widely used in various fields of science and technology due to a fortunate combination of the optical properties of their constituent components 1,2 . Semiconductor quantum dots possess a number of unique photophysical properties, such as, high extinction coefficient (10 5 -10 6 M -1 cm -1 ), high luminescence quantum yield (up to 80%), photostability, and dependence of the spectral properties on the QD size 3 .…”
Section: Introductionmentioning
confidence: 99%